Pneumatization of the temporal portion of the zygomatic arch: The contribution of computed tomography to the reconstruction in volumetric two-dimensional and three-dimensional, with the aid of image rendering protocols - C M Romano-Sousa; E Garritano-Papa (Wolters Kluwer Medknow Publications, 2015)
Pneumatization refers to the asymptomatic development of cavities containing air within them. There is great variability in the extent of temporal bone pneumatization. Nevertheless, in a few cases it extends to the zygomatic process. Images are presented in which the panoramic radiograph and hypocycloidal tomography reveal this variation from the norm, to which professionals must be alert, since the images may simulate the presence of pathology. In this case report we describe the presence of pneumatization of the petrous and zygomatic portions of the temporal bone, demonstrating the contribution of CT to reconstruction in volumetric 2D and 3D, with the aid of image rendering protocols.